S1PR2 deficiency enhances neuropathic pain induced by partial sciatic nerve ligation - GU, Qiang (Turk J Med Sci, 2019)
BACKGROUND/AIM: Sphingosine 1-phosphate receptor 2 (S1PR2), a member of the seven-transmembrane receptor family, can be activated by its natural ligand sphingosine 1-phosphate (S1P) to initiate signal transduction and is involved in a wide range of biological effects such as immune cell migration and vascular permeability. Its relationship with neuropathic pain (NP) has not been reported. In this study, the effects of S1PR2 on the development of NP were studied. MATERIALS AND METHODS: We generated a model of NP by partial sciatic nerve ligation (pSNL). The 50% paw withdrawal threshold of the wild-type (WT) group and the S1PR2 deficiency group were measured at several time points after surgery. The inflammatory factor levels of the two groups were measured by real-time quantitative polymerase chain reaction (RT-PCR). Neutrophil infiltration and glial cell activation were detected by immunofluorescence. Matrix metalloproteinase 9 (MMP9) and its substrate myelin basic protein (MBP) were measured by RT-PCR, western blotting, and immunofluorescence.Result: The S1PR2 deficiency group showed a reduction in 50% paw withdrawal threshold compared with WT mice (P < 0.05) at 3 days after the operation. In the ligated sciatic nerve of the S1PR2 deficiency group, the mRNA expression of IL-1β was increased; the numbers of infiltrating neutrophils and activated astrocytes were also increased. The expression of MMP9 was elevated while MBP was decreased. CONCLUSION: S1PR2 deficiency could increase the pain sensitivity of a NP mouse model and promote the development of NP.